ISOLASI DAN IDENTIFIKASI GOLONGAN SENYAWA TOKSIK DARI DAGING BUAH PARE (Momordica charantia L.) - Gede Bawa, I G. A. (Jurnal Kimia (Journal of Chemistry); Vol. 3, No. 2 Juli 2009, 2012)
Isolation and identification of toxic compounds were conducted to snake fruit (Momordica charantia L.). Maseration of 600 grams dried fruit in methanol resulted in 54.250 grams dark green extract which were toxic to brine shrimp (Artemia salina Leach) with an LC50 = 74.99 ppm. When the extract was dissolved in water and partitioned using n-hexane and chloroform three extracts were obtained. The n-hexane extract was found to be the most toxic to brine shrimp (LC50 = 130.439 ppm). Separation of the n-hexane extract using column chromatography resulted in 7 fractions. The most toxic fraction (F), LC50 = 33.83 ppm, was pure based on TLC. FTIR analyses showed that the active components of the extract contains triterpenoides characterized by CH aliphatic groups (CH2, CH3), binded O-H, C-O, C=C, and C=O. UV-Vis spectra showed absorption at 274,2 and 432,8 nm suggesting an n * electronic transition.
Keywords: toxic compounds, snake fruit (Momordica charantia L.), brine shrimp (Artemia salina Leach)